2018
DOI: 10.1371/journal.pone.0190882
|View full text |Cite
|
Sign up to set email alerts
|

Potential drug-drug interactions and their risk factors in pediatric patients admitted to the emergency department of a tertiary care hospital in Mexico

Abstract: BackgroundDrug-drug interactions (DDIs) detected in a patient may not be clinically apparent (potential DDIs), and when they occur, they produce adverse drug reactions (ADRs), toxicity or loss of treatment efficacy. In pediatrics, there are only few publications assessing potential DDIs and their risk factors. There are no studies in children admitted to emergency departments (ED). The present study estimates the prevalence and describes the characteristics of potential DDIs in patients admitted to an ED from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
30
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 29 publications
6
30
2
2
Order By: Relevance
“…Morales-Rios et al are the only authors who have conducted a study in Mexico. 17 Although both studies included very similar populations and hospital services, they found a higher prevalence than our results. The use of different software to identify pDDIs could explain this difference.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Morales-Rios et al are the only authors who have conducted a study in Mexico. 17 Although both studies included very similar populations and hospital services, they found a higher prevalence than our results. The use of different software to identify pDDIs could explain this difference.…”
Section: Discussioncontrasting
confidence: 49%
“…These authors report in different multivariate models that taking numerous drugs is a risk factor for pDDIs. 17 Santibañez et al, in an observational study conducted in Chile, found a high prevalence of pDDIs in a pediatric intensive care unit where in just 44 patients analyzed, a total of 1240 potential interactions were found and 93.7% of these interactions presented in patients who had been prescribed 10 or more medications. 21 The large number of interactions presented in a small number of patients can be explained by the fact that the severity and complexity of the diseases treated in an intensive care unit requires an aggressive pharmacological approach and patients receiving increasing amounts of medication are more likely to present drug interactions.…”
Section: Discussionmentioning
confidence: 98%
“…The prevalence of potential DDIs (42%) was found be lower than the reported findings of other studies in pediatric hospitals in Mexico (61%) and Philadelphia (49%), but higher than the prevalence of DDIs found in other pediatric studies (3.8%) (5)(6)(7)14). This wide variability in the reported prevalence of DDIs in different studies can be explained by the included population, the underlying medical conditions of the involved patients, the study design, and the software used for their identification (6,12).…”
Section: Discussioncontrasting
confidence: 73%
“…Another study reported that contraindicated DDIs occurred in 5%, major DDIs in 41%, moderate DDIs in 28%, and minor DDIs in 11% of all hospitalizations (6). Also, it was reported that the ratio of 'contraindicated' DDI was 0.2%, 'serious' DDIs were 7.5%, and 'significant-monitor closely' were 62.8% (7). The large difference in the prevalence of clinically important potential drug interactions might be due to the critical medical conditions of pediatric inpatients, which make them more susceptible to the administration of multiple drugs, complex treatment regimens, and care by physicians of different specialties for consultations (15,16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation